ANALISIS LAYANAN DOKUMEN PADA KINERJA AGENSI DI PT. SAMUDERA MAKMUR AGENSI CABANG CILACAP - Habib Al Jaddir; Indah Ayu Johanda Putri; Trisnowati Rahayu (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Ship document services in the context of agency services play a crucial role in maintaining the continuity of ship operations in accordance with the standards set by the International Maritime Organization (IMO). Agent services are responsible for providing various document services that support ship operational activities, starting from the arrival process, maintenance, to ship departure, in accordance with IMO standards. Explaining that quantitative research is a type of research that uses numbers as a means to carry out data analysis. In its application, the figures are analyzed using statistical methods to obtain more measurable and objective information. So that the researcher can identify the influences or relationships that exist in the data, allowing for more quantitative interpretation and generalization to a wider population. So by applying a quantitative approach, the author realizes the aim of validating and measuring the extent to which the y variable in improving port security as an attachment variable can be known and answered. A total of 30 respondents filled out a 2-material questionnaire, each of which contained 9 questions regarding document services and 9 questions regarding agency operations. Filling in the questionnaire is carried out by the ship's crew using agency services at PT. Samudera Makmur Agency Cilacap branch 1. Document services (X) are partially very influential because they have a positive and significant probability of agency performance (Y). Has a positive and significant influence with a regression coefficient of ???? 6.312+0.862X The linear regression equation shows that increasing the level of document service on agency performance at PT. Samudera Makmur Agensi is 0.862 2. Based on the results of the coefficient of determination test to determine the amount of influence exerted by variables X and Y, it is found that the R square value is 0.859 or 85%. This shows the magnitude of the positive influence of the implementation of document services on agency performance..